Optimization of Electronic-Based Government System Architecture (SPBE) In The Application Architecture Domain In XYZ District - Lisdiana, Lisdiana; Firmansyah, Gerry; Mulyo Widodo, Agung; Tjahjono, Budi (Asian Journal of Social and Humanities, 2024)
The Electronic-Based Government System (SPBE) is a government administration that utilizes information and communication technology to provide services to SPBE Users as stipulated in Presidential Regulation No. 95 of 2018. SPBE aims to create an integrated government business process between Central Agencies and Regional Governments, form a complete government unit and produce bureaucracy and high-performance public services. To support the implementation of SPBE, the National SPBE architecture is compiled as a detailed guide that covers technical and methodological aspects, ensuring the integration of government electronic systems. This architecture provides convenience in increasing efficiency and effectiveness, as well as being a guide for SPBE governance in Central Agencies and Regional Governments. The XYZ Regency Government has implemented the SPBE architecture as the basis for implementation in its area. This study analyzes the SPBE architecture in XYZ Regency based on the National SPBE architecture to provide optimization recommendations on the application architecture domain. Despite the existence of Presidential Regulation Number 95 of 2018 and Number 132 of 2022, the preparation of government architecture in Indonesia still faces challenges due to the lack of clear guidance. More detailed references are needed as derivatives of existing regulations to ensure consistent and optimal implementation, help agencies understand and implement the SPBE architecture, so that digital transformation towards Indonesia 4.0 is achieved by 2040.